Predictors of Water Lead Levels in Drinking Water of Homes With Domestic Wells in 3 Illinois Counties. Issue 6 (November 2021) - Geiger, Sarah D.; Bressler, Jonathan; Kelly, Walton; Jacobs, David E.; Awadalla, Saria S.; Hagston, Bart; Onwuta, Uche; Panier, Carey; Dorevitch, Samuel
Abstract : Context: Millions of US homes receive water from private wells, which are not required to be tested for lead (Pb). An approach to prioritizing high-risk homes for water lead level (WLL) testing may help focus outreach and screening efforts, while reducing the testing of homes at low risk. Objective: To (1) characterize distribution of WLLs and corrosivity in tap water of homes with private residential wells, and (2) develop and evaluate a screening strategy for predicting Pb detection within a home. Design: Cross-sectional. Setting: Three Illinois counties: Kane (northern), Peoria (central), and Jackson (southern). Participants: 151 private well users from 3 Illinois counties. Intervention: Water samples were analyzed for WLL and corrosivity. Main Outcome Measures: (1) WLL and corrosivity, and (2) the sensitivity, specificity, and predictive value of a strategy for prioritizing homes for WLL testing. Results: Pb was detected (>0.76 ppb) in tap water of 48.3% homes, and 3.3% exceeded 15 ppb, the US Environmental Protection Agency action level for community water systems. Compared with homes built in/after 1987 with relatively low corrosivity, older homes with more corrosive water were far more likely to contain measurable Pb (odds ratio = 11.07; 95% confidence interval, 3.47-35.31). The strategy for screening homes with private wells for WLL had a sensitivity of 88%, specificity of 42%, positive predictive value of 58%, and negative predictive value of 80%. Conclusions: Pb in residential well water is widespread. The screening strategy for prioritizing homes with private wells for WLL testing is greater than 85% sensitive. Abstract : Supplemental Digital Content is Available in the Text.